Implementation of Innovation Strategy, Intellectual Capital in Efforts to Increase Financial Performance - Renan Lintang Prakoso; Lia Uzliawati; Tri Lestari (PT. EQUATOR SINAR AKADEMIA, 2022)
The purpose of this study is to analyse the influence of innovation strategy and intellectual capital on organizational performance in the context of developing countries. The sample consists of 41 managers of manufacturing companies in the steel industry in the province of Banten, Indonesia. Data were analysed by partial least squares–structural equation modelling. This study provides empirical evidence that the three components of intellectual capital produce a positive and significant effect on firm performance. Structural capital is the component that has the most influence on performance. It also shows a positive and significant relationship between innovation strategy and intellectual capital. Structural capital is also the component most influenced by the innovation strategy. This research uncovers limitations for the future. First, the work uses as the only source of information, consulting at the highest level of the company. Second, this study only covers manufacturing industry companies. The results may have important practical implications for stakeholders and managers and offer a vision of the influence of intellectual capital on the innovative capacity of organizations. The value of work lies in the importance of intellectual capital in a developing country like Indonesia, given the low level of knowledge in this field.